Comics Polysystem in Iran: A Case Study of the Persian Translations of Les Aventures de Tintin - Kenevisi, M. Sadegh; Sanatifar, M. Saleh (Department of Modern Languages and Cultural Studies, University of Alberta, 2016)
With the advent of Polysystem Theory in the 1970s, Translation Studies (TS) experienced a significant transformation. This approach incorporated the sociocultural context into the analysis of translation. The influence of Even-Zohar’s Polysystem Theory (“Polysystem Studies”) was so marked that Bassnett and Lefevere coined the new term “Cultural Turn” to describe the transformation in TS (xxi). As a result of this transformation, translation can no longer be regarded as an accumulation of mere strings of discrete linguistic signs, but rather as a cultural entity that is the outcome of two possibly divergent cultural repertoires. Polysystem Theory envisages culture as a complex network of related systems, of which literature is one. As an internally related and dynamic polysystem, literature forms a network of relations called “literary” (Even-Zohar 28). These relations are composed of the canonized or “central” and non-canonized or “peripheral” strata. In other words, while one literature may occupy a secondary position in the literary polysystem and scarcely affect the polysystem’s central configuration, another literature may come to dominate the centre and develop into a canonical work. According to Even-Zohar, a peripheral position is assumed for translated literature (“Culture Repertoire” 389-403). This peripheral position is postulated to be even more marked for children’s literature, as Even-Zohar considers it to be already situated in a peripheral and secondary place in the literary system of the source culture (“Polysystem Studies” 131).